What’s love got to do with it? A biophilia-based approach to zoonoses prevention through a conservation lens - Kirkey, Jason R. (Frontiers in Conservation Science, 2024)
E.O. Wilson coined the term biophilia, defining it as an innate affinity to the natural world. The concept of nature connectedness is used in environmental psychology as a measure of feelings and self-perceptions of connectedness to nature. Researchers have found a wide variety of positive effects associated with nature connectedness, including better mental health and wellbeing, increased altruistic and cooperative behavior, and heightened empathy. When these feelings of empathy are directed toward nature and applied to conservation actions, they can overcome the effects of compassion collapse, a phenomenon observed to lower study participants willingness to engage in altruistic behavior when there are many or diffuse victims of a disaster. Biophilia is an important concept in conservation, but it has not been widely applied to zoonoses prevention. The public health community has often relied on fear-based (biophobic) messages, which can drive the very interactions they were intended to avoid (e.g., media reports of bat zoonoses leading to culling activities and destruction of bat habitat) and exacerbate the ecological drivers of spillover. Communication strategies rooted in biophilia may be more effective at generating empathy for both ecological and human communities, leading to greater willingness to leave zoonotic pathogen hosts and their habitats alone, further reducing spillover events and the ecological conditions that make spillover more likely. Given the intertwined nature of human and ecological health, it is critical that the conservation and public health communities speak in a unified voice.